Criação de partículas em modelos cosmológicos - Houndjo, Stéphane Jonas Mahouton (2010)
We investigate particle production in an expanding universe dominated by a perfect fluid with the equation of state p = a?. The particle production rate, using the Bogoliubov coefficients, is determined exactly for any value of a in the case of a flat universe. When the strong enegy condition is satisfied, the particle production rate decreases with time; the opposite occurs when the strong energy condition is violated. In the phantom case, the particle production rate diverges at finite time for each mode represented by a wavenumber k. In a first step, in order to compute the energy density associated with the produced particles, we use a cut-off in the Planck scale and find that it tends to zero as the big rip is approached. We conclude that quantum effects due to particle creation are not able to prevent the big rip. In the second step, in order to perform a deep analysis of the quantum effects, we use the n-wave regularization technique for calculating the quantum energy density and find that it becomes the dominant component of the universe near the big rip. We conclude in this case that quantum effects can prevent the occurrence of the big rip. We also investigate the effects of quantum particle production on a classical sudden singularity occurring at finite time in a Friedmann universe. We use an exact solution to describe an initially radiation-dominated universe that evolves into a sudden singularity at finite time. We calculate the density of the created particles exactly and find that it is generally much smaller than the classical background density and pressure which produce the sudden singularity. We conclude that, in the example studied, quantum particle production does not avoid nor modify of the sudden future singularity